Food of Plant Origin in the Life of Early Medieval Bulgarians (End of 7th – Beginning of 11th Century) - Hrissimov, Nikolay (Studia Ceranea, 2017)
The article surveys the available data on food of plant origin used in the period of the First Bulgarian Empire. The information is based on written sources and paleobotanical data, which show the presence of diverse plants used for food. It is also evident that these data are rather scarce compared to those from Byzantium. No food recipes have survived from this period, but there is some secondary evidence allowing the reconstruction of some foods. It suggests that grain porridges, rather than bread, were the main food.